Correlation of bioactive marker compounds of an orally applied Morus alba root bark extract with toxicity and efficacy in BALB/c mice - Langeder, Julia; Koch, Mirijam; Schmietendorf, Hannes; Tahir, Ammar; Grienke, Ulrike; Rollinger, Judith M.; Schmidtke, Michaela (Frontiers in Pharmacology, 2023)
In traditional Chinese medicine, the root bark of Morus alba L. is used to treat respiratory infections. Recently, anti-inflammatory and multiple anti-infective activities (against influenza viruses, corona virus 2, S. aureus, and S. pneumoniae) were shown in vitro for a standardized root bark extract from M. alba (MA60). SanggenonSanggenons C and sanggenon D were identified as major active constituents of MA60. The aim of thisthe present preclinical study was to evaluate, whether these 2 This is a provisional file, not the final typeset article findings are transferable to an in vivo setting. Therefore, MA60 was orally administered to female BALB/c mice to determine (i) the maximum tolerated dose (MTD) in an acute toxicity study and (ii) its anti-influenza virus and anti-inflammatory effects in an efficacy study. A further aim was to evaluate whether there is a correlation between the obtained results and the amount of sanggenonsanggenons C and D in serum and tissues. As a result, the MTD was reached at 100 mg/kg. The tolerance of the MTD was confirmed inIn the efficacy study. However, the antiviral and anti-inflammatory , the treatment effects were not significant.moderate. For the quantitation of sanggenonthe marker compounds sanggenons C and D in serum and tissue samples (liver and lung), an UPLC-ESI-MS method was developed and validated. Dose-dependent quantities of sanggenon C in serum and sanggenon D in liver samples were detected. TheOnly very low concentrations of sanggenonsanggenons C and D were determined in lung samples may prevent MA60 to exert significant antiviral and anti-inflammatory effects. Nonone of these compounds was found in spleen samples. There was no compound accumulation was found when MA60 was administered repeatedly. The herein determined low serum concentration after oral application once daily encourages the use of an alternative application route like intravenous, inhalation or intranasal administration to exploit the full potential of bioactive sanggenons from M. alba root bark as well as their toxicity.and/or multiple dosing in further trials. The herein established method for the quantitation of thesethe marker sanggenon compounds in tissue samples enablesserves as a basis to determine pharmacokinetic parameters such as their bioavailability forin future studies.